Mental accounting and its impact on outbound leisure traveler’s overspending Behavior. - Chu, Peng. (2013)
Using demographics, travel-related, research-related and expenditure-related variables, this research paper examines the variables that affect the probability of overspending among Singapore outbound leisure travelers who practice mental accounting and those who do not. The data collected from 314 random survey respondents across different age group and income levels were analyzed using the binary probit models. Our research concluded three findings that are consistent with previous literature on mental accounting and consumer expenditure pattern. Firstly, we found that mental accounting does leads to higher probability of outbound leisure travelers overspending. Secondly, the absence of mental accounting does not lead to higher probability of outbound tourists overspending. Lastly, outbound tourists who practise mental accounting are more likely to overspend as compared to those who do not.